Здійснення повноважень підрозділами зв'язків із громадськістю МВС України - Лафазан, Ю.О. (Держава і право, 2010)
Зроблено спробу розкрити механізм здійснення функцій підрозділів звязків із громадськістю МВС України. За допомогою порівняльного аналізу українських і зарубіжних юридичних актів зроблено узагальнення відносно діяльності досліджуваних

підрозділів.

Ключові слова: центри звязків із громадськістю, функції центрів, діяльність

центрів. Проанализированы ведомственные нормативно правовые документы, на основании которых делается попытка раскрыть механизм осуществления функций центров

связей с общественности МВД Украины. При помощи сравнительного анализа украинских и зарубежных юридических актов делается обобщение относительно деятельности исследуемых подразделений.

Ключевые слова: центры связей с общественностью, функции центров, функции

центров, деятельность центров. In article departmental is standard legal documents on which basis are analysed attempt
to open the mechanism of realisation of functions of the centres of communications from the
public of the Ministry of Internal Affairs of Ukraine becomes, by means of the comparative
analysis of the Ukrainian and foreign legal certificates generalisation of activity of investigated divisions becomes.
Key words: the centres of public relations, functions, the mechanism of realisation of functions by the centres of public relations, functioning, activity of the centres of public relations.